Hubungan Intensitas Hujan dan Debit Aliran: Studi di Ruas Saluran pada Perumahan Mendalo Park dan Perumahan Bougenville Lestari, Kota Jambi - Lailal Gusri; Elsan Siahaan; Jalius; Bambang Irawan; 2M. Zahari MS (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
The relationship between rainfall intensity and discharge can be seen when it rains, there is runoff in the drainage system. The purpose of the study was to determine the relationship between discharge as a dependent variable to rainfall and water level as an independent variable, the method used was to collect maximum rainfall data for 20 years (2003-2022) from the Sultan Thaha Meteorological Station and the Jambi Climatology Station, rainfall frequency using the gumbel method, normal, log normal and log person type III, determine the coefficient C, concentration time, rainfall intensity, and determine flood discharge and conduct a simple regression analysis. The results of the linear regression test were very strong, which was stated with a P-value of less than 0.05 so that the hypothesis was rejected. In the 2nd recurrence period it was 5.91 x 10-14, which means that it can be concluded that rainfall intensity affects discharge.